The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-49278-8
|View full text |Cite
|
Sign up to set email alerts
|

A Granger causality analysis of groundwater patterns over a half-century

Abstract: Groundwater depletion in many areas of the world has been broadly attributed to irrigation. However, more formal, data-driven, causal mechanisms of long-term groundwater patterns have not been assessed. Here, we conducted the first Granger causality analysis to identify the “causes” of groundwater patterns using the rice-producing parishes of Louisiana, USA, as an example. Trend analysis showed a decline of up to 6 m in groundwater level over 51 years. We found that no single cause explained groundwater patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…For instance, groundwater level may determine the water available for irrigation and plays a critical role in the sustenance of water intensive crops, such as rice. Our findings showed a substantial decline in groundwater level for most study counties ( Fig 1 ), which can be attributed to excessive pumping for irrigation [ 35 36 ]. It is likely that the current rate of groundwater decline may not sustain rice production in the future, highlighting a need to develop sustainable adaption strategies to optimize groundwater usage and to maintain rice yield in the region.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, groundwater level may determine the water available for irrigation and plays a critical role in the sustenance of water intensive crops, such as rice. Our findings showed a substantial decline in groundwater level for most study counties ( Fig 1 ), which can be attributed to excessive pumping for irrigation [ 35 36 ]. It is likely that the current rate of groundwater decline may not sustain rice production in the future, highlighting a need to develop sustainable adaption strategies to optimize groundwater usage and to maintain rice yield in the region.…”
Section: Discussionmentioning
confidence: 97%
“…A modeling study from the North China Plains demonstrated that limiting groundwater irrigation can lead to 40% reduction in crop production [ 32 ]. Recently, causal linkages between groundwater levels and rice yield have been estimated over 50 years in the agricultural regions of Louisiana [ 35 ], where irrigation is mostly dominated by pumping [ 36 ]. At the same time, energy-related variables have been shown to influence the production of agricultural commodities [ 37 – 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…To acquire the maximum causality, we applied the Akaike information criterion (AIC; Akaike (1974)) to automatically select the optimal lag length for each model. Following Singh and Borrok (2019), the maximum lag was calculated as shown in Equation () italicMax0.25emitalicLag=12T10014 where T is the length of the time series. 3.Two‐tailed F tests were used to test the null hypothesis (H 0 : ENSO does not cause runoff signature variation) of Granger causality at the 5% significance level.…”
Section: Methodsmentioning
confidence: 99%
“…To acquire the maximum causality, we applied the Akaike information criterion (AIC; Akaike (1974)) to automatically select the optimal lag length for each model. Following Singh and Borrok (2019), the maximum lag was calculated as shown in Equation ( 2)…”
Section: Granger Causalitymentioning
confidence: 99%
“…Granger-causality is a useful method for capturing statistical relationships between VAR model variables and estimates the degree to which one time series predicts future values of another time series [46, 43, 44, 47]. The statistical test for Granger-causality compares the predictive ability of the time series model of interest with and without the putative causal variable and is therefore interpretable as evidence towards a causal relationship, but not as proof of a causal relationship.…”
Section: Methodsmentioning
confidence: 99%